THE SCIENTIFIC INTERPRETATION OF THE PRINCIPLE OF GENDER EQUALITY IN 20TH-CENTURY HISTORIOGRAPHY - Shamsiyeva M. X (TARIXIY TADQIQOTLAR, 2025)
This article examines the formation of the principle of gender equality and its place in historiography, the development of gender history as an independent field of study since the second half of the twentieth century, as well as the scholarly contributions of researchers such as Joan Wallach Scott, Gerda Lerner, Sheila Rowbotham, Bonnie G. Smith, and Merry Wiesner-Hanks. It is emphasized that in the modern period, gender historiography represents a new scientific paradigm that interprets human history through the principles of equality, intercultural dialogue, and a polycentric approach.